Mophorlogy,mineralogy and engineering characterization of Tanjung Bin fly ash [electronic resource] - 213206 Yap, Shih Lim; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2008